Complete Solution of an Inverse Problem for One Class of the High Order Ordinary Differential Operators with Periodic Coefficients - Efendiev, R.F. (Журнал математической физики, анализа, геометрии, 2006)
The purpose of the present work is to solve the characterization problem, which consists of identi cation of necessary and su cient conditions on the scattering data ensuring that the reconstructed potential belongs to particular class.